SYNTHESIS OF 6-BROMO- AND 8-CHLORODERIVATIVES 4-(HYDROXYPHENYLAMINO)- AND 4-(AMINOPHENYLAMINO)-2- METHYLQUINOLINES (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
The derivatives of 6-bromo- and 8-chloro-4-(hydroxyphenilamino) and        4-(aminophenylamino)-2-methylquinolines are obtained by interaction of 2-methyl- 4-chloroquinolines with o-, m-, p-aminophenoles and o-, m-, p-phenylendiamines.
Keywords: 2-methyl- 4-chloroquinolines; derivatives; o-, m-, p-phenylendiamines